Effect of concomitant dosing with acid-reducing agents and vemurafenib dose on survival in patients with BRAFV600 mutation–positive metastatic melanoma treated with vemurafenib ± cobimetinib. (July 2019) - Lewis, Karl; Hauschild, Axel; Larkin, James; Ribas, Antoni; Flaherty, Keith T.; McArthur, Grant A.; Dréno, Brigitte; McKenna, Edward; Zhu, Qian; Mun, Yong; Ascierto, Paolo A.
Abstract: Background: We conducted a retrospective analysis to evaluate the impact of concomitant acid-reducing agents (ARAs) and vemurafenib dose on the efficacy of vemurafenib in patients with BRAF V600 mutation–positive unresectable or metastatic melanoma treated with vemurafenib or cobimetinib plus vemurafenib. Methods: Data were pooled for patients treated with vemurafenib or cobimetinib plus vemurafenib in the BRIM-2, BRIM-3, BRIM-7, and coBRIM studies. The primary end-points were progression-free survival and overall survival across patient subgroups defined by vemurafenib dose (full vs reduced) and concomitant ARA use (yes vs no). Objective response rate (ORR) was also analysed. Steady-state vemurafenib concentrations were evaluated according to vemurafenib dosing and concomitant ARA use across treatment cohorts in a subset of patients from BRIM-7 and coBRIM with available concentration data. Results: Efficacy analyses included 920 patients: 641 in the vemurafenib cohort and 279 in the cobimetinib plus vemurafenib cohort. Overall, no significant differences in survival outcomes were observed across subgroups according to vemurafenib dose and ARA use, with or without adjustment for known prognostic covariates, in both treatment cohorts. ORR was also similar across subgroups in both treatment cohorts. Steady-state vemurafenib concentrations were analysed in 389 patients (193 in the vemurafenib cohort and 196 in the cobimetinib plus vemurafenib cohort) and were generally similar across vemurafenib dose subgroups, regardless of ARA use in both treatment cohorts. Conclusions: Results of this retrospective pooled analysis suggest that ARAs can be used concomitantly with vemurafenib, alone or in combination with cobimetinib, without compromising the efficacy of vemurafenib. Highlights: Concomitant acid-reducing agents did not affect vemurafenib ± cobimetinib efficacy. Vemurafenib dose reduction did not affect vemurafenib ± cobimetinib efficacy. Acid-reducing agents did not affect steady-state vemurafenib concentrations. Acid-reducing agents can be used concomitantly with vemurafenib ± cobimetinib.